The impact of social capital and collaborative knowledge creation on e-business proactiveness and organizational agility in responding to the COVID-19 crisis - Khaled Saleh Al Omoush; Virginia Simón-Moya; Javier Sendra-García (Journal of Innovation & Knowledge (JIK), 2020)
The purpose of this study is to explore the role of social capital and collaborative knowledge creation in achieving e-business proactiveness in responding to the COVID-19 crisis. An online survey was used to collect data from industries that had to continue working during the crisis, such as the pharmaceutical and cleaning materials sectors. The sample consisted of 198 managers. The findings show that social capital and collaborative knowledge creation have a significant role in achieving e-business proactiveness in responding to the pandemic. The results also show the positive impact of collaborative knowledge creation and e-business proactiveness on organizational agility during the crisis. The present study opens broad horizons for the exploration of emerging themes in information technology studies, including the role of collaborative knowledge creation and e-business proactiveness and their impact on organizational agility in responding to global pandemics. An understanding of the pivotal impact of social capital and collaborative knowledge creation on e-business proactiveness provides managers with valuable insights into managing the pressures of pandemics.
Keywords: 650; Collaborative knowledge creation; COVID 19; e-business proactiveness; Organizational agility; Pandemic; Social capital